Effects of Annealing Temperature on Microstructure and Magnetic Properties of Ni0.05Zn0.95Fe2O4 Nanoparticles - Arda, L.; Dogan, N.; Boyraz, C. (Springer, 2018)
The magnetic behavior of Ni0.05Zn0.95Fe2O4 nanoparticles synthesized by the sol-gel technique route was clarified To figure out the influence of annealing temperature on the structure of Ni0.05Zn0.95Fe2O4 particles, x-ray diffraction (XRD) tool was used and revealed spinel cubic structure without any secondary phases. The particle formation and sizes were obtained using scanning electron microscope (SEM). Elemental composition of the nanoparticles was also provided by an energy-dispersive x-ray analysis tool (EDX). The magnetic behaviors of the synthesized powders annealed at varying temperatures were determined by vibrating sample quantum design PPMS measurement system tool. The M-H curves of the samples showed that the samples had S-shape but they reached no saturation state at the presence even at 30 kOe.
Keywords: NiZn ferrites; Sol-gel; Nanoparticles; Magnetic measurement